Secret Agent for International Maoism: José Venturelli, Chinese Informal Diplomacy and Latin American Maoism. (December 2016) - Rothwell, Matthew
Abstract : The Chilean artist José Venturelli was a supporter of Maoist China. This article, a brief political biography of Venturelli, shows how he acted on behalf of the People's Republic of China's informal diplomacy among Latin Americans and worked to promote Maoist politics among Latin American revolutionaries. The article also advances the hypothesis that Venturelli represents an archetype of the sort of international actor who was key to the globalization of revolutionary politics during the long 1960s.